Selection function of particles under impact loads: The effect of collision angle. (19th May 2018) - Portnikov, Dmitry; Peisakhov, Roman; Gabrieli, Gabriel Ofek; Kalman, Haim
ABSTRACT: The current work investigates the effect of collision angle on the breakage of particles under impact loads. The experiments were performed using a homemade experimental system that accelerates the particles horizontally toward the target using compressed air. The design of the system allows the angle of the target and the air velocity, both adjustable to check different collision angles at different impact velocities; and the tested material that was blown to the target to be collectible for measuring the percentage of broken particles for the analysis. In this study, six different materials were tested by conducting experiments with different collision angles and impact velocities. As expected, the results showed that the collision angle affects the breakage of the particles. When the collision angle becomes acute, i.e., less than 90° (perpendicular collision with the target), it results in less breakage of the particles for all tested materials and at all tested velocities. Consequently, an empirical model got established. This model can predict the median impact velocity that causes half of the particle population to break, depending upon collision angle and particle size.